2019
DOI: 10.1007/s10995-018-02699-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Flexibility and Depression in New Mothers of Medically Vulnerable Infants: A Mediational Analysis

Abstract: Objectives.-Maternal depression in the postpartum period is prevalent and associated with negative child outcomes, including behavior problems and cognitive delays. Mothers of children admitted directly after birth to the neonatal intensive care unit (NICU) are at even higher risk for depressive symptoms and infants born premature and/or at low birth weight may be more vulnerable to the adverse effects of maternal depression. Understanding mechanisms, particularly modifiable mechanisms, involved in the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Lower self‐compassion is associated with symptoms of anxiety and depression (Felder et al, 2016; Monteiro et al, 2019; Psychogiou et al, 2016) and increased parenting stress in mothers (Moreira et al, 2015), whereas higher self‐compassion is linked with better mother–infant attachment (Kordi & Mohamadirizi, 2018). Likewise, lower maternal psychological flexibility is associated with depressive and anxious symptoms (Evans et al, 2012; Monteiro et al, 2019; Shea & Coyne, 2011; Stotts et al, 2019), whereas higher maternal psychological flexibility is associated with greater maternal responsiveness (Evans et al, 2012).…”
Section: The Role Of Compassionmentioning
confidence: 99%
“…Lower self‐compassion is associated with symptoms of anxiety and depression (Felder et al, 2016; Monteiro et al, 2019; Psychogiou et al, 2016) and increased parenting stress in mothers (Moreira et al, 2015), whereas higher self‐compassion is linked with better mother–infant attachment (Kordi & Mohamadirizi, 2018). Likewise, lower maternal psychological flexibility is associated with depressive and anxious symptoms (Evans et al, 2012; Monteiro et al, 2019; Shea & Coyne, 2011; Stotts et al, 2019), whereas higher maternal psychological flexibility is associated with greater maternal responsiveness (Evans et al, 2012).…”
Section: The Role Of Compassionmentioning
confidence: 99%
“…It is likely that mothers who are concerned about one health behavior, such as secondhand smoke, are also concerned about multiple other health behaviors, such as breastfeeding, which may represent a more general perspective with regard to individual and family health. Further, it is possible that interventions targeting one health behavior may positively influence others (e.g., 44 , 45 ). Notably, very few mothers reported concerns about nicotine present in their breastmilk as a reason for stopping breastfeeding, but we did not explore the 46 “other” reasons for breastfeeding cessation, some of which may have been unique concerns for mothers who do not smoke but live with others who do.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that increasing psychological flexibility through mindfulness therapies reduced maternal depression during the NICU admission and after discharge. 58 ACT interventions can be delivered by a variety of trained facilitators, 24 and demonstrate improved mental health outcomes for parents of children with life-threatening illness, 59 asthma 60 and autism. 61 ACT may be more appropriate for parents in the NICU compared with interventions such as cognitive-behavioural therapy, 24 which demonstrates effectiveness in reducing depression but not anxiety for NICU mothers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%